ANALISIS TEKNIK DAN KECEPATAN MENYUNDUL BOLA PADA PEMAIN SEPAKBOLA PPLP ACEH - Dedi Saputra; Zulheri Is (Jurnal Dedikasi Pendidikan, 2021)
Heading the ball is essentially playing the ball with the head. basic techniques of heading the ball, namely: 1) running to pick up the ball with the eye directed at the ball; 2) neck muscles are strengthened / tightened, heading the ball using the touch of the forehead; 3) the body is moved or pulled back, curving at the waist area then by moving the entire body consisting of the explosive power of the abdominal muscles, the pelvic and leg thrusts (knees bent and then straightened) the body is swung or stomped forward so that the forehead is right on the ball, has a posture Good, effective movement techniques will result in good heading and direction in the game of football. This study aims to obtain a series of information on speed in heading the ball, in carrying out the heading of the PPLP Aceh soccer athlete. The method used in this research is descriptive analysis, namely analyzing and presenting data systematically so that it can be easier to understand and conclude. The research subjects were 11 PPLP Aceh soccer athletes. The instruments used in this research are; To obtain speed data in heading the ball with three basic techniques through measuring video recordings, obtained through the help of movie maker software, 675.2 phontom software and the results of analysis of research data through the help of software obtained results